Mechanism of enhanced sensitivity of mutated β‐adrenergic‐like octopamine receptor to amitraz in honeybee Apis mellifera: An insight from MD simulations. Issue 12 (17th September 2022) - Li, Mengrong; Bao, Yiqiong; Xu, Ran; Zhang, Xiaoxiao; La, Honggui; Guo, Jingjing
Abstract: BACKGROUND: Amitraz is one of the critical acaricides/insecticides for effective control of pest infestation of Varroa destructor mite, a devastating parasite of Apis mellifera, because of its low toxicity to honeybees. Previous assays verified that a typical G protein‐coupled receptor, β‐adrenergic‐like octopamine receptor (Octβ2R), is the unique target of amitraz, but the honeybee Octβ2R resists to amitraz. However, the underlying molecular mechanism of the enhanced sensitivity or toxicity of amitraz to mutated honeybee Octβ2R E208V/I335T/I350V is not fully understood. Here, molecular dynamics simulations are employed to explore the implied mechanism of the enhanced sensitivity to amitraz in mutant honeybee Octβ2R. RESULTS: We found that amitraz binding stabilized the structure of Octβ2R, particularly the intracellular loop 3 associated with the Octβ2R signaling. Then, it was further demonstrated that both mutations and ligand binding resulted in a more rigid and compact amitraz binding site, as well as the outward movement of the transmembrane helix 6, which was a prerequisite for G protein coupling and activation. Moreover, mutations were found to promote the binding between Octβ2R and amitraz. Finally, community analysis illuminated that mutations and amitraz strengthened the residue–residue communication within the transmembrane domain, which might facilitate the allosteric signal propagation and activation of Octβ2R. CONCLUSION: Our results unveiled structural determinants of improved sensitivity in the Octβ2R‐amitraz complex and may contribute to further structure‐based drug design for safer and less toxic selective insecticides. © 2022 Society of Chemical Industry. Abstract : This study reveals the implied molecular mechanism of the enhanced sensitivity or toxicity of the insecticide amitraz to mutated honeybee β‐adrenergic‐like octopamine receptor by computational approaches, which will help to establish the underlying principles of G protein‐coupled receptor activation, as well as safe insecticide design.